2020
DOI: 10.3389/fgene.2020.577795
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Haplogroup M7 Confers Disability in a Chinese Aging Population

Abstract: Mitochondrial DNA (mtDNA) haplogroups have been associated with functional impairments (i.e., decreased gait speed and grip strength, frailty), which are risk factors of disability. However, the association between mtDNA haplogroups and ADL disability is still unclear. In this study, we conducted an investigation of 25 mtSNPs defining 17 major mtDNA haplogroups for ADL disability in an aging Chinese population. We found that mtDNA haplogroup M7 was associated with an increased risk of disability (OR = 3.18 [95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…We have previously found that haplogroup M7 was associated with a significant reduction in the risk of liver cancer in Northern China 31 . More recently, Sun et al reported that haplogroup M7 is associated with an increased risk of disability in an ageing Chinese population 32 . In this study, we further found that haplogroup M7 was associated with a reduced risk of CRC.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…We have previously found that haplogroup M7 was associated with a significant reduction in the risk of liver cancer in Northern China 31 . More recently, Sun et al reported that haplogroup M7 is associated with an increased risk of disability in an ageing Chinese population 32 . In this study, we further found that haplogroup M7 was associated with a reduced risk of CRC.…”
Section: Discussionsupporting
confidence: 68%
“…31 More recently, Sun et al reported that haplogroup M7 is associated with an increased risk of disability in an ageing Chinese population. 32 In this study, we further found that haplogroup M7 was associated with a reduced risk of CRC. Thus, our results provide further evidence for the involvement of mtDNA haplogroup M7 in ageingrelated human diseases, especially cancer.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Mitochondrial haplogroup J was associated with a higher risk of obesity in the Qatari population( Dashti et al, 2021 ). Mitochondrial DNA Haplogroup M7 Confers Disability in a Chinese Aging Population( Sun et al, 2020 ). Here, these mitochondrial genomes of A6, A7, and A40 pedigrees belong to the Eastern Asian haplogroups H2, F4b, and M10a, respectively.…”
Section: Disccusionmentioning
confidence: 99%